Ethics and Law: The Intersection of Utilitarianism and Animal Interests - Correa-Martínez, César Alberto (Scientific journal of social studies, 2024)
This article aims to analyze how ethics, from the perspective of utilitarianism, has raised the question of animal welfare, the human-animal relationship and the moral reflections around it, as well as how it is understood. as a moral commitment and its impact on the law. From this starting point, it begins by talking about ethical debates and subsequently makes an analysis of utilitarianism and ethics from the point of view of three authors: Jeremy Bentham, John Stuart Mill, and Peter Singer thus, finally, we focus on Singer’s work in relation to practical ethics and positions regarding human-animal – non-human animal treatment, deducing from it a particular vision that is predominant in current Colombian law. It is also proposed to criticize the utilitarian theory, which however has been the starting point of modern legislation in its commitment to recognize some rights of non-human animals. Due to this position, we currently have concepts such as animal welfare and sentience that were incorporated into the Colombian legal system through the Constitutional Court’s decisions and by the legislator’s provision in Law 1774 of 2016. The methodology is qualitative using the descriptive method. and hermeneutic, since it makes a general assessment of the main themes, while proposing new reading formulas from an ethical and legal perspective that contribute to solutions in understanding human-animal relationships. Finally, it is important to clarify that, although in practice the human is an animal, the meaning used in this writing will be human to refer to the human animal and animal to refer to the non-human animal.